Colloidal photoluminescent refractive index nanosensor using plasmonic effects - Guzatov, Dmitry V. (2020)
Fluorescence enhancement by metal nanostructures which is sensitive to refractive index n of an ambient medium is suggested as an operation principle of a novel refractive index sensor for liquids. Calculations are made for spherical and spheroidal Ag particles, and potential feasibility of sensitivity of the order of Δn=10-4 is demonstrated. Sensors of this type can be made fully colloidal with metal bodies deposited on a substrate or comprising a metal layer covering colloidal assembly of dielectric particles to serve as a test strip as well as placed on a fiber tip end to get local probing of refractive index in the tip-enhanced refractometry mode. Colloidal core-shell semiconductor nanocrystals may become the best candidates for this type of sensors whereas molecular probes may be affected by chemical properties of tested liquids.